2008
DOI: 10.1088/0957-0233/19/11/115801
|View full text |Cite
|
Sign up to set email alerts
|

Highly integrated front-end electronics for spaceborne fluxgate sensors

Abstract: Scientific instruments for challenging and cost-optimized space missions have to reduce their resource requirements while keeping the high performance levels of conventional instruments. In this context the development of an instrument front-end ASIC (0.35 μm CMOS from austriamicrosystems) for magnetic field sensors based on the fluxgate principle was undertaken. It is based on the combination of the conventional readout electronics of a fluxgate magnetometer with the control loop of a sigma-delta modulator fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(16 citation statements)
references
References 17 publications
0
16
0
Order By: Relevance
“…The Magnetometer Front-end ASIC (MFA) was developed in a close cooperation between the IWF magnetometer group and the Fraunhofer Institute for Integrated Circuits (Magnes et al 2008), and is shown in Fig. 6.…”
Section: Digital Fluxgate Magnetometermentioning
confidence: 99%
“…The Magnetometer Front-end ASIC (MFA) was developed in a close cooperation between the IWF magnetometer group and the Fraunhofer Institute for Integrated Circuits (Magnes et al 2008), and is shown in Fig. 6.…”
Section: Digital Fluxgate Magnetometermentioning
confidence: 99%
“…The prototype has outstanding mass and volume characteristics; however, it relies on commercial off-the-shelf components which are not suitable for use in the radiation belts. Magnes et al (2008) describe a highly integrated front-end for a spaceborne fluxgate. The design is very compact, low power and has an excellent parametric radiation tolerance of 170 krad (300 krad functional).…”
Section: M Miles Et Almentioning
confidence: 99%
“…In fact, we may consider our approach as a modification of phase-sensitive detection for arbitrary time window. Even more generalized approach is used in digital signal processing (DSP) magnetometers [12]- [14]. We believe this is the reason why we did not observed increased noise which is otherwise a common disadvantage of time-domain methods.…”
Section: Pulse Excitationmentioning
confidence: 69%